1999
DOI: 10.1037/h0087643
|View full text |Cite
|
Sign up to set email alerts
|

Treatment approaches for obese and overweight African American women: A consideration of cultural dimensions.

Abstract: The purpose of Ms article is to acknowledge the utility of an Afrocentric systems approach to treating obese or overweight African American women. It is suggested that a treatment program should address and integrate the strengths and supports of the culture into the development of interventions. African American beliefs about psychotherapy and family, cognitive and coping styles, religiousness and spirituality, and body satisfaction and body image, as well as current approaches to treating obesity and overwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Learning may be enhanced through relational and group‐based instructional approaches emphasizing social interaction, social learning, and the value of working with others . A key consideration is the extent to which members of an individual's social network will support dietary changes and the priority placed on such changes relative to other family and community responsibilities …”
Section: Cultural Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning may be enhanced through relational and group‐based instructional approaches emphasizing social interaction, social learning, and the value of working with others . A key consideration is the extent to which members of an individual's social network will support dietary changes and the priority placed on such changes relative to other family and community responsibilities …”
Section: Cultural Considerationsmentioning
confidence: 99%
“…This highlights the importance of using instructional elements that resonate with learning preferences. Creating opportunities for participants to generate unique solutions to problematic aspects of their dietary behavior and to share personal narratives or testimonials that allow for self‐expression (e.g., motives for and obstacles to dietary change, and examples of past successful performances) may have added benefits . The persuasive value of testimonials over factual information has been documented, in particular, among individuals who lack motivation to change their dietary behavior …”
Section: Cultural Considerationsmentioning
confidence: 99%
“…One factor that may protect a woman from developing an eating disorder is a reluctance to accept and identify with mainstream culture. This resistance may be helpful in preventing women of color from internalizing and adopting mainstream cultural pressures for dieting and thinness (Davis, Clance, & Gailis, 1999). Abrams et al (1993) reported that, among African Americans, disordered eating was related to assimilation to Caucasian culture, which they measured with the Racial Identity Attitude Scale (RIAS; Helms & Parham, 1990), while Pumariega et al (1994) found that a strong Black identity, measured by a one-item rating, was negatively correlated with a preoccupation with becoming thinner.…”
Section: Acculturationmentioning
confidence: 99%
“…The selfevaluative aspect of body image reflects the positive or negative feelings people have about their body and how satisfied they are with their physical self (McArthur et al, 2005). A previous study by Davis et al (1999) suggested that the greater incidence of obesity among AfricanAmericans is related to greater acceptance of diverse body types in their culture which is protective against the idealization of thinness typically found in the mainstream culture which is predominantly European-American.…”
Section: Article Articlementioning
confidence: 98%